Aqueous‐Phase Synthesis of Mesoporous Zr‐Based MOFs Templated by Amphoteric Surfactants. Issue 13 (26th February 2018) - Li, Ke; Lin, Shaoliang; Li, Yongsheng; Zhuang, Qixin; Gu, Jinlou
Abstract: Zr‐based mesoporous metal–organic frameworks (mesoMOFs) with uniform mesochannels and crystallized microporous framework were constructed in a water‐based system using amphoteric surfactants as templates. Aqueous‐phase synthesis guaranteed the formation of rod‐shaped surfactant micelles. Meanwhile, the carboxylate groups of amphoteric surfactants provided the anchoring to bridge Zr‐oxo clusters and surfactant assemblies. As a result, the directed crystallization of MOFs proceeded around cylindrical micelles and the hierarchical micro‐ and mesostructure was produced. The dimensions of mesopores were easily tailored by changing the alkyl chain length of the applied surfactants. The included surfactant was effectively extracted thanks to the exceptional stability of the obtained Zr‐based mesoMOFs. The almost complete occupation of the mesopore by cytochrome c exemplifies the accessibility of the mesochannels, suggesting the potential applications of the obtained mesoMOFs with bulky molecules. Abstract : Zr‐based mesoporous MOFs with uniform mesochannels and crystalline microporous framework were constructed in a water‐based system using amphoteric surfactants as templates. Amphoteric surfactants not only produced a hexagonal cylindrical mesophase but also offered a coordinating agent chemically anchored to the metal precursor for the directed crystallization of MOFs along surfactant assemblies.